Sistema eletrônico para lâmpadas fluorescentes de indução baseado na topologia sepic half-bridge bi-integrada com controle de intensidade luminosa por modulação de baixa frequência - Fraytag, Jeferson (2015)
This master thesis presents the analysis and design of an electronic drive system for fluorescent induction lamps. This lighting technology, despite being patented since the 60s, is not widely diffused in the market context. However, it is an extremely attractive alternative due to long lifetime and high luminous efficiency. The analysis circuit consists of a power factor correction associated with a power control stage, which provides the lamp ignition and current limitation. An integration methodology is applied in order to reduce the number of active semiconductor switches. The resulting topology, called here SEPIC half-bridge, presents a shared switch able to act, both in the pre-regulator stage, as well as for the power control stage. The number of elements reduction also occurs by magnetic integration. In this case, the pre-regulator inductors are distributed in a single core. For electronic system flexibility, it was inserted the dimming capability, where the low frequency modulation technique was evaluated. This technique is suitable for high power variation rates and provides a stable operation. The topology is controlled by a feedback system ensuring a satisfactory response of the system when subjected to disturbances, in addition to ensuring the correct power to the lamp. The electronic ballast designed behavior was evaluated experimentally. In this situation, there was obtained a low input current distortion associated with a high power factor. The lamp power variation range was 70% (30 W to 100 W), with an average efficiency around 82%.